PROFIL MEDIA SLIDE INTERAKTIF BERBASIS MS. POWER POINT PADA POKOK BAHASAN SUBSTANSI GENETIKA KELAS XII - SUHERMIN (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
The objective of this research are to produces a genetics substance interactive slide media that feasible theoretically. Theoretical feasibility got from a validation media. This research is a development research especially slide interactive development based on Ms. Power Point. The data was collected by using media and materi sheet validation. The results of this research is a genetics substance interactive slide media was feasible theoretically. Theoretical feasibility from validation media and material is 83,75% and 97,5% with category very feasible. Keywords: media, interactive slide, Ms. Power Point, genetics substance